Integration : the key and the way towards life-time engineering - Koukkari, Heli (2008)
The real estate and construction sector is in change that is mainly driven by increasing requirements concerning the performance of constructions during their whole life-time: the overall performance of buildings and constructions need to be managed from cradle to grave, and with a great emphasis on customer and user needs. The true success of the change in relation to demands depends largely upon management of innovations and processes. Methods, tools and skills to handle data and knowledge from various domains have become crucial. In order to have a reliable basis for new practices, research and higher education need to work on science-based approaches. This concerns all aspects from prediction of safe life-time of constructions to methods of integration. This paper gives an overview of relatively new disciplines – like simulation-based engineering science – and technologies – like Building Information Modelling – that can be applied to support life-time engineering through integration and synergy.